Interannual variability in tropospheric nitrous oxide. Issue 16 (27th August 2013) - Thompson, R. L.; Dlugokencky, E.; Chevallier, F.; Ciais, P.; Dutton, G.; Elkins, J. W.; Langenfelds, R. L.; Prinn, R. G.; Weiss, R. F.; Tohjima, Y.; O'Doherty, S.; Krummel, P. B.; et al.
Abstract [1] Observations of tropospheric N2O mixing ratio show significant variability on interannual timescales (0.2 ppb, 1 standard deviation). We found that interannual variability in N2O is weakly correlated with that in CFC‐12 and SF6 for the northern extratropics and more strongly correlated for the southern extratropics, suggesting that interannual variability in all these species is influenced by large‐scale atmospheric circulation changes and, for SF6 in particular, interhemispheric transport. N2O interannual variability was not, however, correlated with polar lower stratospheric temperature, which is used as a proxy for stratosphere‐to‐troposphere transport in the extratropics. This suggests that stratosphere‐to‐troposphere transport is not a dominant factor in year‐to‐year variations in N2O growth rate. Instead, we found strong correlations of N2O interannual variability with the Multivariate ENSO Index. The climate variables, precipitation, soil moisture, and temperature were also found to be significantly correlated with N2O interannual variability, suggesting that climate‐driven changes in soil N2O flux may be important for variations in N2O growth rate.